ANALISIS HUBUNGAN IJTIHAD DAN TAJDID PEMIKIRAN EKONOMI TERHADAP PERKEMBANGAN USAHA (Studi kasus Pada Amal Usaha Organisasi Masyarakat Muhammadiyah) - Dharma Setyawan (Islamic Economics Journal, 2013)
Muhammadiyah declares that the gate of Ijtihad (reasoning) and Tajdid (modernization) were being yet continued. Ijtihad was the base core to establish the main character of Muhammadiyah as a Modern Islamic Modernization Movement. Then, the establishment on Tajdid (modernization) grows as a motor to improve the system of its movement on finding the solution to ideology problem, politic, Business, social, cultural, and defence. Muhammadiyah, which the first time moved on social-religious track, was still upbringing to comprehend and rolling in the progressivity of Moslem society as in the case Indonesia. By Ijtihad (reasoning) and Tajdid (modernization), the role-model of Muhammadiyah as a social-religious movement grows its root on Business practice. The Council of Business and Enterpreneurship (MEK) of Muhammadiyah schedules on developing The House for Charity of Muhammadiyah (AUM). Dawam Rahardjo (2000) confirms, a large number of member and institution will represent as a comparative advantage capital resources to the movement of Muhammadiyah. Those resources orchestrate Muhammadiyah as an organization which is not only moves on social- education-and-religious practices, but as well in Business and Finance. At least, there are two reasons why Muhammadiyah rolls in Business practice Firstly, Muhammadiyah perform to roll in this business merit by the image of intechangible advantages to other charities: as well as schools, hospitals or religious calls. Secondly, Muhammadiyah sustains a potential power to organize those. That is supported by the fact that there are many beureucrates possess in higher structural of Muhammadiyah, the large number of human resources out-put by Muhammadiyah schools, the enterpreneurs possessions, and large number of its members. This thesis researches the influence of Ijtihad (reasoning) and Tajdid (modernization) to the growth of The House for Charity of Muhammadiyah (AUM).